2012
DOI: 10.3892/or.2012.2015
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 and miR-145 inhibit stem cell characteristics of PC-3 prostate cancer cells

Abstract: Emerging evidence demonstrates that cancer stem cells (CSCs) are the critical drivers of tumor progression and metastasis. The microRNAs (miRNAs) may play a crucial role in repressing/promoting metastasis of cancer by regulating CSCs. A previous study showed that miR-143 and miR-145 play an important role in regulating bone metastasis of prostate cancer (PCa), but the exact mechanism of regulation of bone metastasis of PCa is not fully understood. In this study, we found that overexpression of miR-143 and miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 44 publications
6
80
0
Order By: Relevance
“…The miR-143 and miR-145 cluster also jointly suppresses tumor sphere formation and the expression of CSC markers (CD133 and CD44) and core pluripotency factors (Oct4, MYC, and KLF4) in PC3 cells (49). This study has further found that miR-143 and miR-145 inhibits bone metastasis progression of PCa using PC3 cells in vivo by regulating CSC characteristics.…”
Section: Mir-143 and Mir-145mentioning
confidence: 84%
“…The miR-143 and miR-145 cluster also jointly suppresses tumor sphere formation and the expression of CSC markers (CD133 and CD44) and core pluripotency factors (Oct4, MYC, and KLF4) in PC3 cells (49). This study has further found that miR-143 and miR-145 inhibits bone metastasis progression of PCa using PC3 cells in vivo by regulating CSC characteristics.…”
Section: Mir-143 and Mir-145mentioning
confidence: 84%
“…Stabilized HIF1 protein is transported into the nucleus, where it binds to hypoxia response elements (HREs) on DNA and activates VEGF gene transcription. High expression of HIF1a has been reported in thyroid cancer and thyroid cancer cell lines (Huang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, miRNAs are involved in the initiation and progression of various human cancers including prostate cancer [4]. Several miRNAs, namely, miRNA (miR)-34a, miR-148a, miR-221, miR-222, miR-143, miR-145, miR-21, and miR-331-3p, are known to be involved in prostate cancer [5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, miR-34a negatively regulates the tumor-initiating capacity of prostate cancer stem cells.…”
Section: Introductionmentioning
confidence: 99%